Triplet emitters versus TADF emitters in OLEDs: A comparative study. (8th February 2018) - Bizzarri, C.; Hundemer, F.; Busch, J.; Bräse, S.
Graphical abstract: This mini-review aims to give an overview of the possible metallic and metal-free emitters that have been used in OLEDs, focusing on the emission behaviour of such complexes. Abstract: The quest for highly efficient electroluminescent materials that can be used in organic light emitting diodes (OLEDs) has been attracting continuously attention. OLEDs are becoming a considerable market for specialist manufacturer, as a consequence of the growing demand for efficient solution in lighting and displays. Therefore it is very important for material scientists to know how to influence the properties of these devices. This mini-review aims to give an overview of the possible metallic and metal-free emitters that have been used in OLEDs, focusing on the emission behaviour of such complexes.